If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -8y = 6 Solving 9x + -8y = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8y' to each side of the equation. 9x + -8y + 8y = 6 + 8y Combine like terms: -8y + 8y = 0 9x + 0 = 6 + 8y 9x = 6 + 8y Divide each side by '9'. x = 0.6666666667 + 0.8888888889y Simplifying x = 0.6666666667 + 0.8888888889y
| 3*4=3-5 | | -m+2q=-nq | | 4x+6+3=13 | | 2x^2+33x+70=0 | | -4.9t=15+7.6t | | 48-x=47 | | 5474+474= | | x+7=12.3 | | 34573957+577593575= | | 5b+7+7b-6=x | | -7x-3+2=8x-8 | | (7+4x)(2-9x)= | | -6n-2n=24 | | 4(2x-10)=3(3x-5)-31 | | -7(-3x+5)-7x=4(x-9)-4 | | 2x+38=-8(x-1) | | 16=7x+9 | | -4a+7=a+23 | | 10n^2-490=0 | | 18=-5w+2(w-3) | | 1x+5=9 | | 15x+(10-x)=129 | | -2(3s-1)-2=-2(9s+6)-3 | | x-6/4+1=7 | | 6r-7+6r=17 | | graphy=-3(x^2+1) | | x+10.4=19 | | 11t+13=7t+41 | | -7x-8+3x=16 | | x+9.9=18.4 | | -0.2-0.3w=-1.5 | | Y=-3(X^2+1) |